uORF-mediated translational regulation of PERK : implications for cell homeostasis and human disease - Fernandes, Rafael (2020)
Upstream open reading frames (uORFs) are cis-acting elements located within the 5’ leader sequence (or 5’ untranslated region; 5’UTR) of transcripts that can regulate translation of the correspondent main open reading frame (mORF). During basal conditions, uORFs are typically considered to be repressors of downstream translation, as they can impede the ribosomes to access the mORF or even induce mRNA degradation by the nonsense-mediated mRNA decay (NMD) pathway. However, during stress conditions, phosphorylation of the eukaryotic initiation factor 2α (eIF2α) allows the expression of several stress-responsive proteins through uORF-mediated mechanisms, while global mRNA translation is inhibited. During endoplasmic reticulum (ER) stress, for instance, the accumulation of unfolded proteins leads to activation of the ER-resident PKR-like ER kinase (PERK) that phosphorylates eIF2α as part of the stress-protective mechanisms of the unfolded protein response (UPR) and the integrated stress response (ISR). This results in the selective uORF-mediated translation of downstream effectors, like the activating transcription factor 4 (ATF4), the CCAAT-enhancer-binding protein homologous protein (CHOP) and the growth arrest and DNA damage-inducible protein 34 (GADD34), which drive stress resolution or, in the case of a prolonged stress, cell death. The dual role of PERK in regulating cell fate has been reported to be involved in the outcome of several human diseases, including diabetes, neurodegenerative disorders and cancer. Moreover, mutations in the EIF2AK3 gene that encodes PERK have been implicated in the development of the rare genetic disease, Wolcott-Rallison Syndrome (WRS). Interestingly, data from ribosome-profiling (Ribo-seq) studies suggested the existence of uORFs within PERK 5’UTR, which could be involved in the regulation of PERK expression. In this work, we aimed to study the translational regulatory role of five AUG- and three non-AUG-uORFs identified in the PERK 5’UTR and assess its impact in cell homeostasis and human disease. While uORF2 and the non-AUG-uORFs 5, 6 and 7 do not seem to have a significant regulatory role, uORF1, uORF3, uORF4 and uORF8 together present a strong repressive effect over mORF translation in basal conditions, possibly by providing a barrier to the scanning ribosomes and precluding translation reinitiation at the mORF, without affecting the PERK mRNA levels. Curiously, we found that when we induce PERK overexpression, it leads to the spontaneous activation of a portion of PERK in the absence of any stress stimulus, possibly highlighting the biological relevance of its uORF-mediated translational regulation in maintaining its physiological basal levels. Conversely, during stress conditions, increased bypass of uORF1 results in a modest degree of translational de-repression, which may help to counterbalance the increased rate of PERK protein turnover observed in these conditions. We also found that alteration of the PERK uORFs by mutations found in WRS patients modify PERK expression, providing a possible link with the disease phenotype. Finally, we tested the impact of PERK unbalanced expression in the viability of HCT116 cells but, at least in our experimental conditions, no differences were found. Altogether, we provide a new example of a transcript containing uORFs that fine-tune mORF translation. Moreover, we highlight the importance of including 5’UTRs, like the one of PERK, in the screening of disease-related mutations and the necessity of functional studies to assess their relevance in the pathogenesis of human diseases. This may provide vital information for the development of new therapeutic strategies.